PERSEPSI PETANI TERHADAP PENGELOLAAN DAN FUNGSI HUTAN RAKYAT DI KABUPATEN CIAMIS - Budiman Achmad; Hasanu Simon; Dian Diniyati; Tri Sulistyati Widyaningsih (Environmental Research Center (PPLH) of Udayana University, 2012)
Perception could potentially groups the farmers. It is interpreted as a communication process whereas the information transferred is influenced by time. The purpose of the research is to make the forest management more efficiently by finding out the farmer’s perception level and its distribution in Ciamis Regency on the management and the function of privately owned forest. Research was conducted between April to July 2010 at four villages i.e. Ciomas, Neglasari, Kertaharja, Kalijaya in the four districts that are Panjalu, Pamarican, Banjarsari, and Cimerak respectively, which represent the landscape of Ciamis regency. Stratified random sampling was fitted to define the samples and interview using questionnaires involved 20 respondents each village. The result showed that the farmer’s perception on management and function of the forests was very positive, and tends to form the homogenous type. Therefore, the privately owned forest management in the future is getting better and the government should respond it by actively socialize programs to the farmers, involve them in the program building, and advocate the farmers side by side to make the policy generated fit with farmers characters and rationally implemented.